Malaria vaccines: high-throughput tools for antigens discovery with potential for their development (Colombia Medica, 2013)
Malaria is a disease induced by parasites of the Plasmodium genus, which are transmitted by Anopheles mosquitoes and represents a great socio-economic burden worldwide. Plasmodium vivax is the second species of malaria worldwide, but it is the most prevalent in Latin America and other regions of the planet. It is currently considered that vaccines represent a cost-effective strategy for controlling transmissible diseases and could complement other malaria control measures; however, the chemical and immunological complexity of the parasite has hindered development of effective vaccines. Recent availability of several genomes of Plasmodium species, as well as bioinformatics tools are allowing the selection of large numbers of proteins and analysis of their immune potential. Herein, we review recently developed strategies for discovery of novel antigens with potential for malaria vaccine development.